CORRELATION BETWEEN BODY WEIGHT AND ORGAN WEIGHT IN DIGESTIVE SYSTEM OF NORTH SULAWESI LOCAL PIG - Revolson Alexius Mege; Nonny Manampiring; Yermia Semuel Mokosuli (Indonesian Biodiversity Journal, 2021)
North Sulawesi local pigs have good potential because they have a high adaptability to the environment and low-quality feed obtained from processed food remnants of the population. The samples used in this study were local sows from North Sulawesi which were spread on traditional farms. The purpose of this study was to obtain data on body weight of livestock including the weight of organs in the digestive system (stomach, intestine and liver). Body weight data will be correlated with organ weight and intestinal length data. The results showed that the average body weight of the local pigs used in this study ranged from 16.65 ± 0.66 kg with the age of the cattle ranging from 1 year. The results of statistical analysis of the correlation test between body weight and organ weight of local pigs showed a very significant correlation value (P < 0.01). The correlation value shown in the study shows a very strong value in the correlation between body weight and the weight of an empty stomach and a strong correlation value is shown in the correlation between body weight and liver weight and intestine length, meaning that the weight of organs in the body in the digestive system will increase with increase in body weight. Body weight is one indicator of livestock productivity that can be estimated based on the size of the animal's body.